evaluate with explaination
Attachments:
![](https://hi-static.z-dn.net/files/de9/477ee1bbbd1139a8428dfe8eff20fced.jpg)
Answers
Answered by
1
sin^2 theta / cos ^2 theta + cos ^2 theta / sin ^2 theta = tan^2 theta + cot ^2 theta
= 1 - sec^2 theta + 1 - cosec ^2 theta
( tan^2theta = 1- sec^2 theta and cot^2theta = 1 - cosec^2 theta )
= 2 - sec^2 theta - cosec^2 theta
= Sec^2 theta + cosec^2 theta - 2
Lhs = Rhs
= 1 - sec^2 theta + 1 - cosec ^2 theta
( tan^2theta = 1- sec^2 theta and cot^2theta = 1 - cosec^2 theta )
= 2 - sec^2 theta - cosec^2 theta
= Sec^2 theta + cosec^2 theta - 2
Lhs = Rhs
ashwin3414:
THANK YOU
Answered by
1
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/d9f/7e290144387a6f1bfb209333bc3accad.jpg)
Similar questions